اعتماد الشباب الجامعي الليبي على تطبيقات الإعلام الرقمي في التعليم عن بعد دراسة ميدانية-كلية الإعلام جامعة بنغازي نموذجاً - سليمان رابح الشريف صالح (Scientific Journal of University of Benghazi, 2021)
The research sought to shed light on the reality of distance university education through digital media applications and the extent to which university youth depend on these technologies, especially during the exceptional circumstances that have been imposed by the epidemic situation as a result of the widespread of coronavirus or what is known as Covid-19 in its first appearance in Wuhan, China at the end of 2019, and in Libya was appeared in March 2020. The descriptive method was employed in order to describe and analyze the phenomenon under investigation, and then extract results from it by using the questionnaire which was distributed to a simple random sample of 10% Of the total number of students who study in the faculty of media at university of Benghazi, which the size of the sample became (396) participants. The results of the research show that the vast majority of the participants using digital media applications in the distance education process, especially Telegram, Messenger, Facebook, and what Sapp, the communication with members of the teaching staff as well as their classmates to discuss with them was among the most important reasons that pushed them to use these applications.